(untitled) (Latakia University Journal -Biological Sciences Series, 2013)
أجري هذا البحث بهدف دراسة القدرة العامّة والخاصّة على الائتلاف لصفات الغلة الحبية, وارتفاع العرنوس على النبات, وطول العرنوس، وصفة عدد الأيام من الزراعة حتى ظهور 50% من النورات المؤنثة، لخمسة عشر هجيناً فرديّاً من الذرة الصفراء ذات الحبوب بيضاء اللون (السلمونية) أنتجت باستخدام طريقة التهجين نصف المتبادل بين ست سلالات مربّاة داخليّاً خلال موسم 2010، وذلك في قسم بحوث الذرة التابع للهيئة العامّة للبحوث العلميّة الزراعيّة في دمشق. قيّمت الهجن الفرديّة في موسم 2011 تحت موعدين لإضافة السماد الآزوتي (يتضمن الموعد الأول إضافة 50% من كمية السماد الآزوتي مع الزراعة، و50% بعد شهر من الزراعة، ويتضمن الموعد الثاني إضافة 50% من كمية السماد الآزوتي بعد 18 يوماً من الزراعة، و50% بعد شهر من الزراعة) حيث نفّذت التجربة بتصميم القطّاعات الكاملة العشوائيّة وبثلاثة مكررات وخلصت النتائج إلى ما يأتي: أظهرت السلالات الأبوية والهجن المستنبطة تبايناً عالي المعنوية لجميع الصفات المدروسة دلالة على التباعد الوراثي بين السلالات الأبوية وبينت نسبة تباين القدرة العامة على الائتلاف إلى تباين القدرة الخاصة على الائتلاف σ2GCA/σ2SCA سيطرةَ الفعل الوراثي التراكمي على وراثة جميع الصفات المدروسة، ما عدا صفة الغلة الحبية حيث سيطر الفعل الوراثي اللاتراكمي على طريقة توريثها. أبدت السلالات CML.330 وIL.26-09 وCML.334 قدرة عامة جيدة على الائتلاف لصفة الغلة الحبية بالنسبة للاستجابة للسماد في الموعدين المدروسين، أظهرت ستة هجن قدرة خاصة جيدة على الائتلاف لصفة الغلة الحبية تحت ظروف الموعد الأول كان أفضلها الهجين IL.215-09 CML.368 ×، أما تحت ظروف الموعد الثاني فقد أظهرت سبعة هجن قدرة خاصة جيدة على الائتلاف لصفة الغلة الحبية كان أفضلها الهجين IL.26-09 CML.330 ×، وقد تفوق الموعد الثاني معنوياً على الموعد الأول لإضافة السماد الآزوتي في صفة الغلة الحبية. This research aimed to evaluate the general and specific combining ability components for six inbred lines and 15 hybrids produced by a half diallel cross method, and was conducted during 2010-2011 seasons, in the Department of the Maize Researches at G.C.S.A.R. Damascus . The evaluation included the grain yield, ear height, ear length, and silking under two different treatments of nitrogen fertilizer (1- addition of 50% of N-fertilizer with sowing and the other 50% one month after sowing. 2- addition of 50% of N-fertilizer 18 days after sowing and 50% one month after sowing).and 3 replicates. Results indicated that: Mean squares of inbred lines, and hybrids were highly significant for all studied traits under two adding dates of nitrogen fertilizer, which indicated the presence of genetic distance among parental lines. The ratios (σ2GCA/σ2SCA) showed that additive gene effect was more important than non-additive gene effect in controlling all studied traits except grain yield which showed dominance of non-additive gene effect under tow dates. Many of significant positive GCA effects were obtained for all traits, therefore, it could be concluded, that the inbred lines CML.330, IL.26-09 and CML.334 seemed to be the best general combiners for grain yield. The hybrid (CML.368 × IL.215-09) had showed the best specific combining ability effects for grain yield under the first date, while the hybrid (CML.330 × IL.26-09) showed the best SCA effects under the second date. The second adding date of nitrogen fertilizer (50% 18 days after sowing and 50% one month after sowing) had surpassed of the first date (50% with sowing and 50% one month after) with significant effects for grain yield trait.